2017
DOI: 10.5897/ajar2017.12657
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organic manure formulated from goat manure on growth and yield of tomato (Lycopersicum esculentum)

Abstract: The influence of organic hydroponic nutrient solution on tomato growth and yield was studied using a randomized complete block design (RCBD) with three treatments (organic nutrient solution, conventional hydroponic fertiliser (as positive control) and plain tap water (as negative control)) replicated three times. Determinate tomato seeds were germinated and transplanted into the 3 treatments. Twenty days after transplanting, vegetative response variables were recorded at fifteen days intervals from each treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Isso se deve ao fato deste substrato proporcionar o aumento significativo do teor médio de água no solo, por ser eficaz na melhoria da estrutura física do solo com a presença da matéria orgânica e atividade microbiológica (Mertens et al, 2017). O esterco caprino, por outro lado, contém elementos essenciais necessários para o crescimento das plantas, incluindo N, P, K, Ca e Mg (Mowa et al, 2018).…”
Section: Resultsunclassified
“…Isso se deve ao fato deste substrato proporcionar o aumento significativo do teor médio de água no solo, por ser eficaz na melhoria da estrutura física do solo com a presença da matéria orgânica e atividade microbiológica (Mertens et al, 2017). O esterco caprino, por outro lado, contém elementos essenciais necessários para o crescimento das plantas, incluindo N, P, K, Ca e Mg (Mowa et al, 2018).…”
Section: Resultsunclassified
“…These results are agreed with Koesriharti and Istiqmah (2016) stated that the nutrient content also affects the growth and yield of pakcoy on hydroponic substrate, because the nutrient solution is one of the most important determining factors on the yield and quality in hydroponic system. Edgar et al (2017) also noted increased growth and yield performance of tomato grown on goat manure.…”
Section: Total Yieldmentioning
confidence: 86%
“…It has been demonstrated that using microorganisms to degrade organic nitrogen in organic sources such as manure results in nitrates and ammonium production which in turn are used for plant production [13]. Organic fertilizers are farmyard manure (FYM), sheep manure (SM), poultry manure (PM), goat manure (GM), chicken manure (CM), and composts among others have been used for crop production for centuries.…”
Section: Introduction 1background To the Studymentioning
confidence: 99%
“…Organic fertilizers are farmyard manure (FYM), sheep manure (SM), poultry manure (PM), goat manure (GM), chicken manure (CM), and composts among others have been used for crop production for centuries. The use of these forms of fertilizers certainly pre-date chemical (mineral) fertilizers, which is of the more recent development in comparison with organic fertilizers [13]. Organic fertilizers are more environmentally friendly since they are from natural and organic sources.…”
Section: Introduction 1background To the Studymentioning
confidence: 99%